Promoting exercise among older Malaysians using text messages / Andre Matthias Mueller - Andre Matthias, Mueller (2016)
Using mobile technology to promote exercise has been effective. However, evidence is largely drawn from studies with young age groups in high-income countries. Using mobile phone text-messaging to promote exercise in older adults in a developing country is promising because mobile phone proliferation is high and many older adults are keen to use this technology. My primary study objective was to examine the effects of mobile phone text-messaging on an exercise intervention on weekly exercise frequency in older Malaysians. Secondary objectives were to investigate in what ways the text messages impacted study participants’ exercise frequency, and to examine the effects of the intervention on secondary outcomes. The Malaysian Physical Activity for Health Study (myPAtHS) was a 24-week, 2-arm parallel randomized controlled trial conducted in urban Malaysia. I recruited participants via health talks in residential associations and religious facilities. Non-exercising, mobile phone using, older Malaysians between 55 and 70 years, were eligible to participate in the study. Participants randomly allocated to the SMS condition received an exercise booklet and 5 weekly text messages over 12 weeks. The content of the text messages was derived from effective behaviour change techniques and further informed by formative pilot studies. Text messages ceased after 12 weeks. No-SMS condition participants received only the exercise booklet. Home visits were conducted to collect outcome data: (1) exercise frequency (primary outcome) and duration, and interview data at Weeks 12 and 24, (2) exercise self-efficacy, physical activity related energy expenditure, sitting time, BMI, grip and leg strength at baseline, and at Weeks 12 and 24. I analysed quantitative data per protocol using various regression models. A total of 43 participants were randomized into the SMS condition (n = 22) and No-SMS condition (n = 21). Intervention unrelated injuries forced four participants to discontinue after a few iv weeks. Overall retention was 86% (37/43). At Week 12 SMS condition participants exercised significantly more than No-SMS participants, 1.21 times, BCa 95% CI [0.18, 2.24], d = 0.76. The semi-structured interviews revealed that the text messages had influenced SMS condition participants who experienced exercise barriers. They described the text messages as being encouraging, a push, and a reminder. At Week 24 there was no significant difference between the research condition (mean difference 0.58, BCa 95% CI [-0.35, 1.55]), d = 0.39. There were no significant effects of the text messages on secondary outcomes. This study provided evidence that text-messaging is effective in promoting exercise in older adults from an upper-middle-income country, Malaysia. Although the effect of the text messages were not maintained when the text messages ceased, the results are promising and warrant more research on behavioural mobile health in older adults and other regions.